Systemic treatment for metastatic castrate resistant prostate cancer: Does seqence matter?. Issue 5 (13th January 2020) - Andrews, Jack R.; Ahmed, Mohamed E.; Karnes, R. Jeffrey; Kwon, Eugene; Bryce, Alan H.
Abstract: Background: Optimal sequencing of systemic therapy in the management for metastatic castration resistant prostate cancer (mCRPC) remains poorly elucidated. The CHAARTED and STAMPEDE studies have proven that early chemotherapy in the hormone‐sensitive setting yields a greater net survival advantage than docetaxel for mCRPC. In a retrospective study, we attempt to investigate the two most common treatment sequences for mCRPC and investigate whether earlier chemotherapy for mCRPC is consequential to survival outcomes. Methods: We identified 112 patients with mCRPC treated at the Mayo Clinic between 2011 and 2017. We identified two cohorts, 80 patients (group A) received full course docetaxel chemotherapy followed by second generation hormone therapy (2nd gen androgen deprivation therapy [ADT]; Abiraterone or Enzalutamide) and 32 patients (group B) treated with 2nd gen ADT followed by docetaxel. The primary endpoint evaluated was 3‐year cancer‐specific survival. Results: Mean prostate specific antigen at initiation of first treatment was 32.0 in group A and 21.7 in group B ( P  = .4). Bone metastases were more prevalent in group B (87% vs 58%, P  = .01). All other clinicopathologic variables were statistically similar between group A and group B. Three‐year cancer‐specific survival was 87.4% vs 64.1% for group A and group B, respectively ( P  = .016). We report a univariate hazard ratio of 3.61 (95% CI, 1.74‐9.5,  0 P  = .01). Three‐year overall survival was 82.4% and 60.8% for group A and group B, P  = .01. These results held true when excluding patients with lymph node only metastasi. Conclusion: Our data indicates that sequence of systemic therapy may influence outcomes for mCRPC and that docetaxel should be considered before 2nd generation ADT. Our results support the importance of earlier chemotherapy in the castration resistant state.